Catalán, vasco y gallego en Menéndez Pidal y los coautores del "ALPI" - Abad, Francisco (Revista de lenguas y literaturas catalana, gallega y vasca, 2020)
Inventariamos y ordenamos las referencias que se encuentran en los textos de Ramón Menéndez Pidal y sus discípulos inmediatos de los años del Centro de Estudios Históricos, a las otras lenguas peninsulares (catalán, vasco y gallego) In this paper we have collected and classiied all references to other peninsular languages (Catalan, Basque and Galician) by Ramón Menéndez Pidal and his closest pupils during the years at the Centre for History Studies.